Bioresponsive microlasers with tunable lasing wavelength. Issue 3 (13th January 2021) - Yuan, Zhiyi; Tan, Xiaotian; Gong, Xuerui; Gong, Chaoyang; Cheng, Xin; Feng, Shilun; Fan, Xudong; Chen, Yu-Cheng
Abstract : A novel mechanism to achieve active lasing particles with controllable functions and tunable wavelengths was developed, paving a new road for biological and biomedical analysis via laser emission. Abstract : Lasing particles are emerging tools for amplifying light–matter interactions at the biointerface by exploiting its strong intensity and miniaturized size. Recent advances in implementing laser particles into living cells and tissues have opened a new frontier in biological imaging, monitoring, and tracking. Despite remarkable progress in micro- and nanolasers, lasing particles with surface functionality remain challenging due to the low mode-volume while maintaining a high Q -factor. Herein, we report the novel concept of bioresponsive microlasers by exploiting interfacial energy transfer based on whispering-gallery-mode (WGM) microdroplet cavities. Lasing wavelengths were manipulated by energy transfer-induced changes of a gain spectrum resulting from the binding molecular concentrations at the cavity surface. Both protein-based and enzymatic-based interactions were demonstrated, shedding light on the development of functional microlasers. Finally, tunable lasing wavelengths over a broad spectral range were achieved by selecting different donor/acceptor pairs. This study not only opens new avenues for biodetection, but also provides deep insights into how molecules modulate laser light at the biointerface, laying the foundation for the development of smart bio-photonic devices at the molecular level.